Model for inflation estimation, case of México - Avilés Ochoa, Ezequiel; Espinoza Audelo, Luis F; Gil Lafuente, Anna María; León Castro, Ernesto; Merigó, José M (2021)
Inflation has been an interest issue for countries since the novel by Fiedman (1977) on the relationship between inflation and growth, and how these factors influence other variables such as employment and business outcomes (Grier and Perry, 2000; 2018). The use of a formulation that can include historical data and inflation expectations in the same result will be important.